2020
DOI: 10.1111/1346-8138.15683
|View full text |Cite
|
Sign up to set email alerts
|

Development of a light‐weight deep learning model for cloud applications and remote diagnosis of skin cancers

Abstract: Skin cancer is among the 10 most common cancers. Recent research revealed the superiority of artificial intelligence (AI) over dermatologists to diagnose skin cancer from predesignated and cropped images. However, there remain several uncertainties for AI in diagnosing skin cancers, including lack of testing for consistency, lack of pathological proof or ambiguous comparisons. Hence, to develop a reliable, feasible and user‐friendly platform to facilitate the automatic diagnostic algorithm is important. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…The values of achieved average accuracy for actinic keratoses was 92.3%, basal cell carcinoma was 91.8%, squamous cell carcinoma was 95.1%, melanoma was 94.2%. In 2020, Huang et al [30] had developed a convolution neural network and had achieved an accuracy of 85.8% and More et al [31] had achieved an accuracy of 75.03% on HAM10000 dataset. In future, the accuracy of the proposed model can be improved by applying the noise removal filter in the pre-processing stage.…”
Section: Comparison Of Proposed Model With Three Resnet Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of achieved average accuracy for actinic keratoses was 92.3%, basal cell carcinoma was 91.8%, squamous cell carcinoma was 95.1%, melanoma was 94.2%. In 2020, Huang et al [30] had developed a convolution neural network and had achieved an accuracy of 85.8% and More et al [31] had achieved an accuracy of 75.03% on HAM10000 dataset. In future, the accuracy of the proposed model can be improved by applying the noise removal filter in the pre-processing stage.…”
Section: Comparison Of Proposed Model With Three Resnet Modelsmentioning
confidence: 99%
“…They had worked on four pre-trained models such as Inception-v3, ResNet-50, Inception-ResNet-v2 and DenseNet201 and had achieved an accuracy of 81.29%, 81.57%, 81.34% and 73.44% respectively. Huang et al [30] had developed a convolution neural network and had achieved an accuracy of 85.8% and More et al [31] had achieved an accuracy of 75.03% on HAM10000 dataset. In this paper, a model is proposed and pre-trained networks are used for detection of skin disease.…”
Section: Introductionmentioning
confidence: 99%
“…The authors achieved an F2-score sensitivity of 91.7% and 89.5% respectively for skin magnifier with polarized light and advanced dermoscope images. The authors in [ 132 ] used DL techniques to build a skin cancer classification model for binary and multiclass classification of malignant and benign skin tumors. They used Kaohsiung Chang Gung Memorial Hospital and HAM10000 datasets in their study.…”
Section: Current Applications Of Deep Learning In Cancer Diagnosis Prognosis and Predictionmentioning
confidence: 99%
“…In the end, they concluded that the training of deep learning models with the best setup of hyperparameters could be performed better than even ensemble models. Hsin et al [ 33 ] presented the automatic lightweight diagnostic algorithm for skin lesion diagnosis. The presented algorithm was more reliable, feasible, and easy to use.…”
Section: Introductionmentioning
confidence: 99%